Universiti Sains Malaysia undergraduates’ thinking styles: A case study. - Shuib, Munir
The distinction of higher (tertiary) education and education in pre-school, primary school and secondary school lies in one of the objectives of higher education that seeks to teach students how to think rather than what to think (Bassham et al., 2005; Munir, 2007).